Newborn skin care practices performed by parents or caregivers: a survey study - Coelho, Rosimar Cabral; Oliveira, Marcia Ferreira Correa de; Ramos, Mily Constanza Moreno (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To analyze the skin care practices of healthy full-term newborns performed by parents and/or caregivers. Method: This is a descriptive, analytical, and cross-sectional study. The sample consisted of 72 parents or caregivers of newborns from five Basic Health Units. A specific questionnaire containing questions about sociodemographic data and newborn skin care practices was constructed and validated in content. The association between the variables was performed using the Shapiro-Wilk test and Fisher's exact test, considering a significance level of 5%. Results: Of the 72 parents or caregivers included in the study, the majority (91.7%) were women, with a mean age of 37.8 years (SD=12.2). Regarding skin care practices, 95.8% usually observe the newborn's skin. For body hygiene, 55.6% reported using soap. When caring for the umbilical stump, most people use 70% alcohol, especially after bathing (36.6%). In the perianal region, most people use some product to clean the area (36.1%), and 86.1% use cream or ointment to protect this region. Conclusion: It was found that the practices of parents and/or caregivers are diverse and are not always consistent with the recommendations of scientific evidence.